Dealing the Crisis Together: The Meaning of Family Support for Employees Infected by Covid-19 - Destri Ayu Kristina; Candra Indraswari (UIN Sunan Kalijaga, 2022)
During the COVID-19 pandemic, family support is needed especially for those who are infected by Covid-19. This study aimed to comprehend the meaning of family support for employees infected with COVID-19. The study used qualitative method with a phenomenological approach. Online and offline interviews were conducted to collect the data. This research had three main informants who work at Company X and each informant was followed by one significant other. The result showed that although the support of each family was different, the meanings that appeared in the three informants had similarities. The three informants interpreted family support as a motivation to come back home and to be healthy again. In addition, all informants interpreted family support as a stress reliever during isolation. In all informant’s views, their family had provided support for them, although in different ways for each informant. Therefore, the main factor influencing the recovery of the informants was family support and only family who always stay and accept their situation. In the end, family support is also interpreted as a spirit when informants face discrimination in their workplace. From the experience of all informants, it is known that family support makes a huge contribution to the recovery process when informants were infected by COVID-19.Abstrak. Saat pandemi seperti ini dukungan keluarga sangat dibutuhkan, terlebih bagi mereka yang sedang terinfeksi COVID-19. Penelitian ini bertujuan untuk memahami dan mengetahui makna dari dukungan keluarga bagi karyawan yang terinfeksi virus COVID-19. Informan dalam penelitian kali ini adalah tiga karyawan yang positif terpapar COVID-19. Penelitian menggunakan metode kualitatif dengan pendekatan fenomenologi dengan menggunakan teknik wawancara secara online dan offline. Penelitian ini memiliki tiga informan utama yang bekerja di Perusahaan X dan masing-masing informan diikuti oleh significant other. Hasil menunjukkan bahwa meskipun dalam bentuk perlakuan setiap keluarga berbeda, namun makna yang muncul pada ketiga informan memiliki kesamaan. Ketiga informan memaknai dukungan keluarga sebagai motivasi untuk kembali pulang dengan sehat kembali. Selain itu, informan memaknai dukungan keluarga sebagai penghilang stress saat isolasi. Bagi semua informan, keluarga akan selalu memberikan dukungan kepada mereka meskipun dengan cara yang berbeda-beda untuk setiap informan. Oleh karenanya, faktor utama yang mempengaruhi kesembuhan informan adalah dukungan keluarga. Hanya keluarga yang selalu bertahan dan menerima keadaannya. Pada akhirnya, dukungan keluarga juga dimaknai sebagai semangat menghadapi diskriminasi yang diterima informan di tempat kerja. Dari pengalaman seluruh informan diketahui bahwa dukungan keluarga memberikan kontribusi yang sangat besar dalam menjalani proses pemulihan ketika orang terinfeksi covid-19.